Territorial development strategies: encouraging origin products through public policies and social participation - Enríquez Caballero, Yuritzi Paola (2019)
This article presents a theoretical approach on the importance of territorial development policies to promote origin products, acknowledging they can, in turn, be an instrument to enhance development. If an origin product promotes the economic development of the territory, it benefits the population through employment, which, in turn, improves people’s wellness or quality of life. At the same time, socio-cultural characteristics encourage development of an origin product, since they give products identity. Consequently, a qualitative methodology is used to identify various approaches, such as heritage and products of quality linked to geographical origin, multifunctional virtuous circle of quality, global value chains, and global production networks. In addition, the importance of these policies in the interaction between institutions and social participation is analyzed.